Допоміжні засоби, які забезпечують якісне друкування - Канінець, А. А. (ХНУРЕ, 2024)
This work is devoted to the consideration and formation of a list of auxiliary materials that accompany the printing process and significantly affect the quality of printed products. Its goal is to form more complete knowledge among students of specialty 186 “Vidual Science and Printing” in this area, to use it in the preparation and defense of qualifying works in this specialty. These products are produced by well-known manufacturers in the printing services market and are grouped according to functional characteristics. Their properties that have the greatest positive effect on the printing process are given.
Keywords: друкування; printing process